Основные причины возникновения микроплазм в pn переходе кремниевых диодов - Марат Тагаев; Али Абдреймов; Жасмина Хожамуратова (Academia One, 2024)
Assumptions that the emission of light from microplasma is closely related to impact ionization, because with the disappearance of light emission, impact ionization also disappears. The change in the current-voltage characteristic associated with the appearance of microplasma decreases with increasing ambient temperature, and therefore the additional conductivity associated with microplasma decreases. At sufficiently high temperatures, the break in the current-voltage characteristic, corresponding to the appearance of microplasma, disappears and, in connection with this, the temperature dependence of the breakdown voltage or current also changes.
Keywords: avalanche breakdown; microplasma; dislocations